Os círculos de leitura como dispositivo para formação de leitores críticos nos anos finais do ensino fundamental - Pinho, Áurea Cristina Bezerra da Silva (2024)
This research's theme is literary literacy and its delimitation is reading circles as a promotion of literary literacy for students in the 7th grade of elementary school at a municipal public school in Caucaia, Ceará. This investigation is justified by the need to use school as a space to contribute to the formation of critical readers according to Cosson (2018), Kleiman (2007), Bortoni-Ricardo (2008) among others, as this is the space in which students they learn in a systematized way, since in their homes, in general, this learning is not possible, even if they have access to technological tools, the presence of the teacher is necessary for this systematization of knowledge. To achieve the objectives and answer the research questions, we sought educational documents that supported this work, such as the PCN, the BNCC, the DCRC, in addition to a theoretical-methodological contribution for an adequate basis such as action research (Thiollent, 2011). The main objective was to systematize reading circles, with regard to literary literacy, through the Basic Sequence proposed by Cosson (2018) and in the analysis of the layers of the text in the light of Sociodiscursive Interactionism – ISD, proposed by Bronckart (2012). To this we add the interactive reading class, proposed by Leurquin (2014), to specifically analyze the categories of textual production and enunciative mechanisms, especially the voices that emanate from the text from the literary work “Extraordinário”, by R. J. Palacio made available by the latest PNLD Literary, from 2019. In Braggio (1992), this research finds the conceptions of reading to which it is affiliated: the interactionist, in which the reader is active and uses their already acquired knowledge and the knowledge arising from the text, being the practice of reading with a focus between the reader and the author of the text; and sociopsycholinguistics, in which the practice of reading focuses on a new event of resignification between reader and text. In discussions about reading and reader training, the relevance of the work developed by Petit (2019) is emphasized, regarding the importance of reading, in addition to literary literacy; Kleiman (1995; 2002; 2007; 2008) from the perspective of Applied Linguistics; Soares (2003; 2009), from the perspective of Education; and Smith (1989) to understand a psycholinguistic analysis of reading aimed at the teacher's pedagogical intervention in learning. To analyze the results of this investigation, we opted for observation techniques based on student participation, description and reflective analysis of the data collected through teaching material developed by the researcher and which culminated in a pedagogical notebook aimed at the teacher (The). It is considered that this research work was satisfactory, even though it does not solve all the problems related to reading, it contributed in a significant in terms of the students' experience in leafing through each page of a literary work, considered extensive by them, in addition to being able to analyze it collectively, produce the meanings of the text in an expressive way and transpose this knowledge into a theatrical piece. With this, students were able to go through literary literacy and realize that reading can spark imagination, pleasure and reflection on their own lives and the environment in which they live.